EFEKTIFITAS MEDIA REALIA UNTUK MENINGKATKAN PEMAHAMAN MENGENAL WARNA BAGI ANAK TUNAGRAHITA SEDANG - Fela Ismiyanti (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract: This research is motivated by being retarded children who are not familiar with color. This study aims to improve understanding about colors red, yellow and blue with the right and see if the media realia can be applied to increase understanding about colors.This research uses experimental research in the form of Single Subject Research (SSR) with ABA design. Subjects were retarded children were X-class DII / C. Target behavior in this study is the ability of the child to know the color of the states, shows and, classifying colors, assessment is provided in the form of a percentage (%). This research was first seen on the baseline condition (A1) the child's ability to recognize colors beginning. After that proceed in the intervention condition further condition to be treated. And further on the baseline condition (A2) that the child's condition after being given treatment without the use of realia media. The data obtained were processed with graphs. So that the results of this research can be clearly defined.  Having analyzed the data obtained the following results at baseline phase (A1) that the child is not able to recognize the colors red, blue and yellow. In the intervention phase that is doing the learning using realia media with a nine-day observation that children can recognize red and blue and yellow color grouping (a value of 77%). And the baseline phase (A2) for five days observation that children are able to recognize the colors red and blue and yellow color grouping (a value of 77%) by not using realia media. It means that learning to use realia media effectively applied to improve understanding about colors for children with intellectual challenges are. Researchers suggest to teachers and researchers in order to provide further learning using realia media to recognize colors in further learning. Kata-kata kunci: media realia; warna; anak tunagrahita sedang.